Analysis of Video Animation Media Development Requirements from a Constructivism Perspective - Pradana, Hirnanda Dimas (Belantika Pendidikan, 2022)
This study aims to see the needs related to developing animated video media. This qualitative descriptive research was conducted using a survey method between May and July 2022. Questionnaires were used to collect data in this study. The research subjects were 90 undergraduate students of Educational Technology at Surabaya State University. The research concluded that animated video media based on the constructivism approach is needed in learning media courses. Students need learning media that can accommodate their learning needs and be used anywhere and anytime. Animated videos are necessary because students feel that these learning media can increase their motivation to learn. Students can form their knowledge using a constructivist approach using animated video learning media.